Temporal and spatial characteristics of droughts and floods in the Loess Plateau based on standardized precipitation index - Changde LI; Lei WANG; Xiaoxia LI; Qisan LI; Zhen CHANG; Zhen MA (暴雨灾害, 2020)
Based on the monthly precipitation data of 57 stations in the Loess Plateau from 1961 to 2018, this paper introduces the standardized precipitation index (SPI) and several assessment indicators of droughts and floods to study the temporal characteristics of the frequencies, the trend characteristics, the changes of the range and intensity of droughts and floods in the Loess Plateau. The spatial and topographical distribution characteristics of annual and summer frequencies and variable trend of droughts and floods are also obtained. The research shows that the droughts frequency of the Loess Plateau is higher than that of floods, the frequencies of summer droughts and summer floods are the highest among the seasons, severe droughts often occur in summer and spring, severe floods often occur in spring and autumn. Overall, the Loess Plateau tends to be arid in the past 58 years, and the trends are also the same in seasons and months. Droughts and floods alternately appeared in the 1960s and 1980s, the number and the intensity of droughts increased in the 1990s. Since the beginning of the 2000s, the drought has eased, and there is a change from drought to flood in the 2010s.The ratio of drought stations and the intensity of drought tend to increase and then decrease, while the ratio of flood stations and the intensity of flood tend to decrease and then increase. In the 1990s, the drought was the heaviest, while in the 1960s, the flood was the heaviest. The zone where droughts and floods happened frequently and the area of significant trend are also obtained by the research, frequencies of droughts and floods in the undulating terrain are generally higher than that in the gentle terrain in summer.